Prebiological Organization of Molecules in Models and in the Matter of the Origin of Life - A. Zhogol, R; ., . (International Journal of Engineering and Technology, 2018)
The theoretical model of cell formation in cell selection is considered. The phenomenology of the process shows that molecular evolution did not have a Darwinian basis for development. According to the described model, cell formation is an inevitable process that develops a clear molecular mechanism. This mechanism is observed throughout the entire period of early development, beginning with the stage of initiation of the process, then at the stage of molecular complications and at the final final stage. The mechanism reveals the ideological concept according to which at an early stage there was a group of ribosome structures catalyzing reversible aminoacyltransfer, their activity led to the formation of a self-replicating cycle on a translational basis.Â Â